The Contribution of the Pediatric Oncology Healthcare Spaces to the Psychosocial Wellbeing of Mothers in the Egyptian Context - Adly, Yara (AUC Knowledge Fountain, 2023)
This study sheds light on the significant contribution of the pediatric oncology healthcare spaces to the psychosocial wellbeing of mothers in the Egyptian context. The research focuses on understanding the experiences of mothers in the different encountered stages during the hospitalization of their children to identify their psychosocial needs and wants. The complexity of healthcare facilities drives the designers to give the humane aspects such as the psychological and social wellbeing second priority. Despite the significant parental role in promoting their children’s health and wellbeing, only few studies explored the contribution of the built environment in response to the parental experiences and needs during their children’s hospitalization process. This study aims to draw attention to the importance of considering the psychosocial needs of the mothers while designing the spaces of the pediatric oncology healthcare settings. It proceeds with the core question: What is the contribution of the pediatric oncology healthcare spaces to the psychosocial wellbeing of mothers who accompany their children during their hospitalization journey in the Egyptian context? Ulrich’s (1991) theory of supportive design along with its associated stress inducing factors were used to guide the process. A descriptive phenomenological approach was adopted where participant observation, including physical and behavioral mapping, was conducted across two Egyptian pediatric oncology healthcare settings. These were followed by in depth interviews (n = 46) with the mothers. This approach addressed the differing psychosocial needs and experiences of mothers during three stages of hospitalization of their children; ‘adjusting to the unknown’, ‘accommodating to the status quo’, and ‘weaving through the ordinary life’, which were studied in three different spatial layouts; Single inpatient rooms, double inpatient rooms, outpatient chemotherapy units. Key questions addressed mothers’ mundane experiences, utilization of spaces, and the contribution of the studied spaces to the psychosocial needs and wellbeing of mothers. Results disclosed common psychosocial needs and demands yet with different intensities across the three hospitalization stages. The dominating factors influencing the contribution of the pediatric oncology healthcare spaces to the psychosocial wellbeing of mothers include issues such as privacy and perceived control, territoriality and personalization, the quality of mother-child relationship, access to social support, and access to restorative resources. Overall, as perceived by mothers, the studied spaces promote differing intensities of contributions to the psychosocial wellbeing of mothers in the Egyptian pediatric healthcare settings. Moreover, mothers’ cultural values, behaviors, and traditions play an essential role in the discussion of the contribution of the pediatric oncology healthcare spaces to the psychosocial wellbeing of mothers. Keywords: Pediatric oncology healthcare spaces, Psychosocial wellbeing, Psychosocial needs, Mothers, Pediatric healthcare facilities, Phenomenology, Ethnographic field tools, Egyptian culture